Efficiency Analysis of Government Expenditure in Districts/Cities of West Nusa Tenggara Province: A Dea Approach (2021-2023) - Indriani, Annisa Ulfa; Muhsyaf, Saipul Arni (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the level of efficiency of local government spending in the health and education sectors of districts/cities in West Nusa Tenggara Province (NTB) using the Data Envelopment Analysis (DEA) approach for the 2021-2023 period. This study uses secondary data, which is analyzed by Constant Return to Scale (CRS) with output-oriented assumptions to evaluate the relative efficiency of 10 districts/cities. The results showed that the level of efficiency of regional expenditure in the health sector was only Central Lombok Regency and East Lombok Regency which achieved a perfect efficiency score when viewed from the output of health outcomes (in this study Life Expectancy and Number of people with health insurance and Maternal Mortality Rate) and inputs (health expenditure budget and number of health workers). In terms of education expenditure efficiency, Bima City is the only city in West Nusa Tenggara that reaches the perfect efficiency level, when viewed from the Average Years of Schooling, School Participation Rate and Expected Years of Schooling as outputs, education expenditure budget and number of schools as inputs. Meanwhile, other regions in West Nusa Tenggara are still at the low efficiency level.